2021
DOI: 10.1101/2021.04.29.442030
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic consequences of domestication of the Siamese fighting fish

Abstract: Siamese fighting fish, commonly known as betta, are among the world's most popular and morphologically diverse pet fish, but the genetic processes leading to their domestication and phenotypic diversification are largely unknown. We assembled de novo the genome of a wild Betta splendens and whole-genome sequenced multiple individuals across five species within the B. splendens species complex, including wild populations and domesticated ornamental betta. Given our estimate of the mutation rate from pedigrees, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 108 publications
0
6
0
Order By: Relevance
“…In bettas, recently, two papers (Kwon et al, 2021;Zhang et al, 2021) showed that the most of heterozygous individuals are male, which supports that in such specie, the male phenotype could be formed by heterogametic sexual chromosomes (XY/XX). However, even when XX vs XX cross was performed, 10% of offspring were male, confirming an incomplete genotypic sex determination in betta (Kwon et al, 2021).…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…In bettas, recently, two papers (Kwon et al, 2021;Zhang et al, 2021) showed that the most of heterozygous individuals are male, which supports that in such specie, the male phenotype could be formed by heterogametic sexual chromosomes (XY/XX). However, even when XX vs XX cross was performed, 10% of offspring were male, confirming an incomplete genotypic sex determination in betta (Kwon et al, 2021).…”
Section: Introductionmentioning
confidence: 80%
“…In bettas, recently, two papers (Kwon et al, 2021;Zhang et al, 2021) showed that the most of heterozygous individuals are male, which supports that in such specie, the male phenotype could be formed by heterogametic sexual chromosomes (XY/XX). However, even when XX vs XX cross was performed, 10% of offspring were male, confirming an incomplete genotypic sex determination in betta (Kwon et al, 2021). Zhang et al (2021) also find in minor proportions homogametic males in their study, which, according with authors, suggest the influence of environmental factors in sex determination in this species.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…This increased complexity is produced through a combination of structural colors, melanin pigments, and non-melanin pigments, and it relies on multiple types of specialized color-producing cells in the skin [11][12][13][14][15]. Color cell development has been characterized to some extent in fish [16][17][18], and genes controlling the use of non-melanin pigments have been identified in a few species of fish and birds [19][20][21][22][23][24][25]. The genetics and development of non-mammalian color patterns are less well understood in other vertebrates, particularly in reptiles [although see [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…This increased complexity is produced through a combination of structural colors, melanin pigments, and non-melanin pigments, and it relies on multiple types of specialized color-producing cells in the skin [11][12][13][14][15]. Color cell development has been characterized to some extent in fish [16][17][18], and genes controlling the use of non-melanin pigments have been identified in a few species of fish and birds [19][20][21][22][23][24][25]. The genetics and development of non-mammalian color patterns are less well understood in other vertebrates, particularly in reptiles [although see [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%